KONSTITUSI MADINAH: LATAR BELAKANG DAN DAMPAK SOSIAINYA - Ahmad Khairuddin (Pascasarjana UIN ANTASARI Banjarmasin, 2007)
This srudy views the sociat history behind the binh of Madinah Charrer aid its impacts in life and civics. Th;s constitution is a written agreement between the lrropher and yastrib community which began *,ith a longjprocess, among the non conducive social condition rhat necded an arbitrary. although ii is very simpte, this constitution has a very significant impact since its irteal principles are stiU relevant in solving roday,s civic problems.